Stability Analysis for Distributed Secondary Control with Consideration of Diverse Input and Communication Delays for Distributed Generations in a DC Integrated Energy System - Wang, Tao; Rong, Chunyan; Tang, Shuai; Hong, Yinqiu (Frontiers in Energy Research, 2021)
Integrated energy system is a promising approach to synthesize various forms of energies, where cooperative control is indispensable for stable and efficient operation. During the information exchange of cooperative distributed secondary control (DSC) in integrated energy system, the effect of time delays on system performance cannot be ignored, which mainly consists of input delays and communication delays. Compared with most of the existing literature which address DSC considering communication delays only, this paper investigates the stability robustness of integrated energy system in case of both input and communication delays. First, the impacts of input and communication delays on DSC are analyzed based on Gerschgorin theorem and Nyquist criterion, where the system stability is dependent on input delays principally while has little correlation with communication delays and the inconsistency of the two delays may result in steady-state deviation. Then, on the assumption of identical input and communication delays, a closed-loop small-signal model equipped with distributed secondary controller is established for stability analysis and the delay-dependent criteria are formulated to determine the stability margin of the system based on critical characteristic root tracking. By a series of trial declarations, the delay margins with regard to different controller gains are determined and the qualitative relationship between delay margins and controller gains can be utilized to guide the controller design for improved system performance. The effectiveness of the theoretical results is verified by case studies on a test system.